The Bruton's tyrosine kinase inhibitor ibrutinib exerts immunomodulatory effects through regulation of tumor-infiltrating macrophages - Ping, Lingyan (Oncotarget, 2017)
The Bruton's tyrosine kinase (Btk) inhibitor ibrutinib has demonstrated promising efficacy in a variety of hematologic malignancies. However, the precise mechanism of action of the drug remains to be fully elucidated. Tumor-infiltrating macrophages presented in the tumor microenvironment have been shown to promote development and progression of B-cell lymphomas through crosstalk mediated by secreted cytokines and chemokines. Because Btk has been implicated in Toll-like receptor (TLR) signaling pathways that regulate macrophage activation and production of proinflammatory cytokines, we investigated the immunomodulatory effects of Btk inhibitor on macrophages. Our results demonstrate that Btk inhibition efficiently suppresses production of CXCL12, CXCL13, CCL19, and VEGF by macrophages. Furthermore, attenuated secretion of homeostatic chemokines from Btk inhibitor-treated macrophages significantly compromise adhesion, invasion, and migration of lymphoid malignant cells and even those not driven by Btk expression. The supernatants from Btk inhibitor-treated macrophages also impair the ability of endothelial cells to undergo angiogenic tube formation. Mechanistic analysis revealed that Btk inhibitors treatment downregulates secretion of homeostatic chemokines and cytokines through inactivation of Btk signaling and the downstream transcription factors, NF-κB, STAT3, and AP-1. Taken together, these results suggest that the encouraging therapeutic efficacy of Btk inhibitor may be due to both direct cytotoxic effects on malignant B cells and immunomodulatory effects on macrophages present in the tumor microenvironment. This novel mechanism of action suggests that, in addition to B-cell lymphomas, Btk inhibitor may also have therapeutic value in lymphatic malignancies and solid tumors lacking Btk expression.